Nepal’s Import Demand Sensitivity to Exchange Rate Fluctuations: An ARDL Co-integration Approach - Bishwakarma, Sagar; Nepal, Pramshu; Bashyal, Devid Kumar (Butwal Campus Journal, 2024)
This study investigates the import demand function for Nepal using a time series econometric approach over 34 years (1990–2023). The analysis employs the ARDL model to estimate the relationship between the import demand of Nepal and key determinants such as remittances, real exchange rate, exchange rate volatility, and Indian inflation. The results show that Nepal’s import demand is income-elastic for remittances and price-elastic for exchange rates, with a significant J-curve effect observed for exchange rate depreciation. Exchange rate volatility positively affects imports, suggesting speculative behavior by importers. Indian inflation has a modest positive impact on imports, reflecting Nepal's dependence on Indian goods. Diagnostic tests confirm the robustness of the model, with no issues of autocorrelation, multicollinearity, or heteroskedasticity. The study’s policy implications emphasize the need for exchange rate stability, managing remittance flows for productive use, controlling domestic inflation, and diversifying trade partnerships to reduce reliance on Indian imports. These measures could help mitigate external shocks and foster long-term economic stability.